Clinical relevance of ethanol coingestion in patients with GHB/GBL intoxication. (10th October 2019) - Galicia, Miguel; Dargan, Paul I.; Dines, Alison M.; Yates, Christopher; Heyerdahl, Fridtjof; Hovda, Knut Erik; Giraudon, Isabella; Wood, David M.; Miró, Òscar; ,; ,; Anand, Jacek Sein; et al.
Highlights: Co-ingestion of ethanol increases the adverse effects of patients intoxicated by GHB/GBL. The most common features were reduction in consciousness. Patients with ethanol co-ingestion had a higher frequencies of arrivals by ambulance, reduction in consciousness, need for treatment in the ED, use of sedatives, admission to critical care units, and prolonged hospital stay. Abstract: Objective: Ethanol intake can increase the sedative effects of gamma-hydroxybutyrate / gamma-butyrolactone (GHB/GBL), although the real clinical impact is unknown. We studied the clinical impact of the co-ingestion of ethanol in patients presenting to the Emergency Department (ED) with acute toxicity related to GHB/GBL use. Method: We performed a secondary analysis of the Euro-DEN Plus Registry (14 countries, 22 EDs) which includes 17, 371 consecutive patients presenting to the ED with acute recreational drug toxicity over 39 consecutive months (October 2013 – December 2016). We compared the epidemiological and clinical characteristics and ED management of patients identified as presenting with acute toxicity related to lone GHB/GBL (Group A) or GHB/GBL combined with ethanol (Group B) without other concomitant drugs. Results: A total of 609 patients were included (age 32 (8) years; 116 women (19%); Group A: 183 patients and Group B: 426). The most common features were reduction in consciousness (defined as Glasgow Coma Score <13 points: 56.1%) and agitation/aggressiveness (33.6%). Those with ethanol co-ingestion were younger patients (Group A/B: 31.5/33.1 years, p = 0.029) and ethanol co-ingestion was associated with a lower frequency of bradycardia (23.5%/15.7%, p = 0.027) and more frequent arrival at the ED by ambulance (68.3/86.6%; p < 0.001), reduction in consciousness (58.9%/49.1%; p = 0.031), need for treatment in the ED (49.2%/60.4%; p = 0.011), use of sedatives (20.1%/12.8%; p = 0.034), admission to critical care units (22.4%/55.3%; p < 0.001), and longer hospital stay (stay longer than 6 h: 16.9%/28.4%; p = 0.003). Conclusions: Co-ingestion of ethanol increases the adverse effects of patients intoxicated by GHB/GBL, leading to greater depression of consciousness, need for treatment, admission to the ICU and longer hospital stay.